Panduan Pengukuran Halal Lifestyle: Pedoman Literasi Keuangan Syariah dan Literasi Halal: Halal Lifestyle Measurement Guide: Guidelines for Islamic Financial Literacy and Halal Literacy - Irmadatus Sholekhah; Dibyo Waskito Guntoro (Neraca: Jurnal Pendidikan Ekonomi, 2023)
All these aspects of life are actually inseparable in the routine activities of a Muslim; that is called the halal lifestyle. The term "halal lifestyle" is yet to be commonly established but is explicitly and implicitly mentioned in the Quran and Hadis as well. Therefore, this paper will proposed the measurement and validity approach for halal lifestyle. The halal lifestyle in foods and beverages will be analyzed and discussed from a halal perspective based on Islamic financial literacy and halal literacy guidance. This study will become a basic reference for measuring the halal lifestyle, which has not been widely discussed by researchers. A total of 108 expert respondents were involved in the research process by completing self-evaluation questionnaires. Islamic financial literacy and halal literacy will be measured using true or false test questions, while the concept of measuring halal lifestyle is carried out using four Likert scales with the choices of strongly disagree, disagree, agree, and strongly agree. Then, confirmatory factor analysis (CFA) will be used to analyze the scoring using SPSS version 21 to test the construct validity. This study is attempted to contribute towards new theoretical knowledge especially in proposing the measurement items for halal lifestyle. This study also has an empirical contribution to understanding the level of literacy among consumers, especially in the halal lifestyle concept.